Strategi Guru Dalam Mengatasi Tantangan Pembelajaran Di SMP 18 Kota Bengkulu - Asmara Yumarni; Aisah Natalia Syafitri; Neneng Puspa Ratih; Iin Komala Dewi; Jaka Rizkiawan Harianda (Universitas Muhammadiyah Gresik, 2025)
This research aims to analyze the strategies used by teachers in overcoming learning challenges at SMP 18 Bengkulu City. Challenges in learning can come from various factors, including limited resources, differences in student characteristics, and changes in the curriculum. Using a descriptive qualitative approach, this research collected data through interviews, observation and document analysis. The research results show that teachers apply various strategies such as the use of innovative learning methods, differentiation approaches, and the use of technology as a learning medium. Apart from that, support from the school and parental involvement also play a role in successfully overcoming learning challenges. It is hoped that this study will provide insight for educators in improving the effectiveness of the learning process in schools.